SISTEM INFORMASI ADMINISTRASI DATA KEPENDUDUKAN PADA KANTOR KELURAHAN KOLURSARI - Erri Wahyu Puspitarini; Majida Noviyanti; Asmania DewiIndria Winata (SPIRIT, 2018)
Problems in the district office Kolursari is manual population data administration system cause inefficiency in processing, data retrieval and archiving letters, so we need a system that is expected to help solve the problem. This research focuses on two things: the population administration and the creation of multiple certificate. Based on system testing was done using a black-box testing which resulted in an average success rate.Keyword : Data, Population Administration, Black-box Testing.